Recent advances in the design of single-atom electrocatalysts by defect engineering - Li, Wei; Chen, Zhikai; Jiang, Xiaoli; Jiang, Jinxia; Zhang, Yagang (Frontiers in Chemistry, 2022)
Single-atom catalysts (SACs) with isolated metal atoms dispersed on supports have attracted increasing attention due to their maximum atomic utilization and excellent catalytic performance in various electrochemical reactions. However, SACs with a high surface-to-volume ratio are fundamentally less stable and easily agglomerate, which weakens their activity. In addition, another issue that restricts the application of SACs is the low metal loading. Defect engineering is the most effective strategy for the precise synthesis of nanomaterials to catch and immobilize single atoms through the modulation of the electronic structure and coordination environment. Herein, in this mini-review, the latest advances in designing SACs by defect engineering have been first highlighted. Then, the heteroatom doping or intrinsic defects of carbon-based support and anion vacancies or cation vacancies of metal-based supports are systematically evaluated. Subsequently, the structure–activity relationships between a single-atom coupled defect structure and electrocatalytic performance are illustrated by combining experimental results and theoretical calculations. Finally, a perspective to reveal the current challenges and opportunities for controllable preparation, in situ characterization, and commercial applications is further proposed.